The Effect of Herding Behavior and Anchoring Bias on Stock Decision-Making in the Capital Market with Risk Tolerance as a Mediating Variable - Gastiadirrijal, Rakan; Andarwati (Jurnal Management Risiko dan Keuangan, 2025)
This study aims to determine the effect of herding behavior and anchoring bias on investment decisions with risk tolerance as an intervening variable on Generation Z in the Jabodetabek. This type of research is explanatory research that aims to test existing hypotheses to find casual relationships between variables. This study used a sample of 143 respondents obtained through online distribution. The data analysis technique used is Partial Least Square (PLS) using the SmartPLS version 4.0 tool. The results of this study indicate that the herding behavior and anchoring bias variables have a significant direct effect on investment decisions. The herding behavior and anchoring bias variables also have a significant effect on risk tolerance. The risk tolerance variable has a significant effect on investment decisions. The test results also show that risk tolerance mediates the relationship between herding behavior and anchoring bias on investment decisions.